Respostas

2013-07-17T15:26:24-03:00
Numa Progressão Geométrica,um termo qualquer é definido pela fórmula:
an=a1*q^(n-1)
Onde
an= termo pedido
a1=primeiro termo
q= razão
n= quantidade de termos.

Logo
a)
a1=4
a2=a1*q >> a2= 4*3 >> a2=12
a3= a1*q^2 >> a3= 4 * 3^2>> a3= 4*9>> a3=36
a4= a1*q^3 >> a4=4*3^3 >> a3= 4*27 >>a4= 108
a5= a1*q^4 >> a5=4*3^4>> a5=4*81>> a5= 324

b)
a1=20
a2=a1*q>> a2= 20*-2 >> a2=-40
a3=a1*q^2 >> a3= 20*-2^2>> a3= 20* -4>> a3=-80
a4= a1*q^3 >> a4= 20*-2^3>> a4= 20* -8>> a4= -160
a5= a1*q^4 >> a5= 20*-2^4>> a4= 20* -16>> a4= -320

2 5 2